Elasticity and Plasticity Behaviors of the Orthodontic Arch Wires - Hussain A Obaidi; Sarmad S Al-Qassar (University of Mosul, College of Dentistry, 2011)
Aims: To evaluate the mean value and compare the: elasticity and plasticity of the Nickel Titanium and Elgilloy arch wires after emersion in artificial saliva for one , two and four weeks. Materials and Me-thods: The sample consisted of 80 piece of Nickel Titanium and Elgilloy wires; Each wire divided into four groups (10 wires for each group: control. one, two and four weeks of emersion in artificial saliva). The specimens were tested with tensile procedure and plotted the load stress- strain curve, form this curve can calculate the elasticity modulus, elasticity limit and plasticity limit. The results were subjected to the descriptive statistics, ANOVA and Duncan's Multiple range analyses at p≤ 0.05 significant level. Results: The Results demonstrated that the modulus of elasticity, elasticity limit and plasticity limit of the Nickel Titanium and Elgilloy arch wires decrease significantly as the emersion time in the artificial saliva increase. Conclusions: The decrease of the biomechanical properties (mod-ulus of elasticity, elasticity limit and plasticity limit) of the Nickel Titanium Elgilloy arch wires which subjected to the artificial saliva did not encourage the using of these arch wires clinically for long time.